Efektivitas Kompres Lidah Buaya terhadap Nyeri Pembengkakan Payudara pada Ibu Post-Partum di Klinik Theresia - Verawaty Fitrinelda Silaban; Merlin Carmila; Otilia Telaumbanua; Puspita Yuli Yanti Harahap (JUMANTIK (Jurnal Ilmiah Penelitian Kesehatan), 2021)
The problem that is often experienced by post-partum mothers is the problem of breast swelling pain. Breast engorgement often causes pain, which makes post-partum mothers often delay breastfeeding their babies. The purpose of this study was to determine the efficacy of aloe vera compress on post-pregnancy breast swelling at the Theresia Clinic, South Nias. This study used a quasi-experimental design with pre-test and post-test with a control group. In this study, the population was 80 people, namely post-partum mothers. The sampling technique was purposive sampling. The data collection technique was carried out using the Visual Analog Scale (VAS). Effectively used to measure the pain scale of breast swelling in post-partum mothers. The results of statistical tests with an independent T test with a = 0.05 obtained a sig value of 0.000 which means a sig value <0.05, therefore there is a significant effect between before and after being given aloe vera compresses on breast swelling pain in post-partum mothers. partum at the Theresia Clinic, South Nias. Aloe vera compress can be suggested as a complementary treatment to reduce the severity of breast engorgement in mothers after childbirth.Keywords: aloe vera compress; breast-feed; breast swelling pain